IMPLEMENTASI PROGRAM CORPORATE SOCIAL RESPONSIBILITY DALAM PENYELENGGARAAN KESEJAHTERAAN MASYARAKAT - ', Iswiyati Rahayu (Jurnal Ilmu Administrasi Negara, 2014)
Implementation of Corporate Social Responsibility Program for the Operation of Society Welfare. This study aims to determine the implementation of Corporate Social Responsibility (CSR) and its impact on the welfare of society. This research uses descriptive qualitative approach to generate data and information that reliable and valid. Techniques of data collection using interviews, observation and discussion of data sources is key informants taken with snowball sampling method of the enterprise, government and society. Data were analyzed using the interactive method. The results showed that the Program Implementation of Corporate Social Responsibility (CSR) is not implemented optimally. Still found problems in economic development, land acquisition and environment that led to the conflict between the company, government and society. Keywords: program implementation, social responsibility, community welfare, conflict.